MINERALOGICAL AND GEOCHEMICAL STUDIES OF AGBAJA IRONSTONE FORMATION NUPE BASIN, CENTRAL NIGERIA (1994)
Agbaja Ironstone Formation of the Lokoja district, Central Nigeria occurs within the Upper Cretaceous sedimentary sequences of the NW-SE trending Nupe Basin. Three lithostratigraphic units were delineated; Lokoja Sandstone (the oldest), Patti Formation and Agbaja Ironstone Formation. Lokoja Sandstone rests unconformably on the basement complex and grades from conglomerate to arkosic sandstone. Patti Formation consists of intercalations of sandstone, siltstone and carbonaceous mudstone units. Agbaja Ironstone Formation is made up of colites, pisolites and bog ore. Textural studies show a very finely to very coarsely skewed mesokurtic sands for Lokoja Sandstone and leptokurtic for Patti Formation. ZTR index value ranges from 61 to 81% for Lokoja Sandstone and 83 to 95% for the Patti Formation. Higher ZTR index value for Patti Formation indicates a relative higher mineralogical maturity over the Lokoja Sandstone. These sedimentological studies indicate a basement source for the sedimentary materials deposited under low energy short fluvial regime, that evolved into two facies; alluvial fans and flood basin. Four petrographic varieties of the Agbaja Ironstone Formation were identified; ooidal pack-ironstone, pisoidal packironstone, detrital mud-ironstone and breccia mud-ironstone Kaolinite ooids are spherical, oblong and fragmented, usually with pseudomorphs of goethite after pyrite at the core. Goethite pisoids cemented in kaolinitic to goethitic matrix are elliptical, oval, subspherical in shape and composite in nature. Constituent minerals of the mud-ironstone are kaolinite, quartz and heavy minerals. Paragenetic studies show that pyrite, siderite, kaolinite, quartz, mica and heavy minerals are the initial minerals of the ironstone while secondary enrichment minerals are goethite, hematite, goyazite-crandallite, bolivarite and boehmite. Chemistry of these minerals further classified them into ferritic kaolinite, kaolinitic ferrite and ferrite. Si02 ranges between 23.71 and 56.41 % and AI203 between 22.01 and 36.54% in all the unferruginized portions of the Agbaja ironstone. But both components can jbe as low as 0.22% in the ferruginized equivalent. Si02 and AI203 contents are highest in the mud-ironstone varieties and lowest in the pack-ironstone varieties. Fe203 content increases from about 1.59% in the unferruginized to about 97.54% in the ferruginized equivalents, for all the petrographic varieties. The highest concentration of Fe203 is in the pisoidal pack-ironstone. P20S values range between 0% in the unferruginized to 5.10% in the ferruginized portions, and often increase with increasing Fe203 contents. MgO, CaO, MnO, Na20 and K20 are generally less than 1.0% in all the petrographic varieties. Element mobility during ferruginization indicates that iron enrichment is accompanied by a parallel depletion in Si02 and AI203, moderate to extreme reduction in CaO, MgO, MnO, Na20 and K20 and a significant gain in P205. This relationship confirms the supergene nature of the replacement process (desilicification, removal of alumina and iron enrichment process (ferruginization). Sedimentological, mineralogical and geochemical studies provided evidences for a kaolinitic precursor for the ironstone deposit, contrary to the earlier proposed chamositic precursor. Also the presence of pseudomorphs of pyrite in nuclei and as incorporation into the concentric laminae of ooids are reliable indicators for a possible accretionary model for the formation of ooids and pisoids prior to ferruginization. Two ferruginization periods unrelated to lateritization were established; first won enrichment is supply due to oxidation of the initial pyrite/siderite and reconcentration of absorbed FeOOH in the lattice structure of kaolinite; second period is linked to the presence of bacteria (framboids) which is oxidised to form iron phosphate complex in the bog ore. The Fe and P were remobilised into the underlying pack-ironstone by descending meteoric water.